Hydration for prevention of kidney injury after primary coronary intervention for acute myocardial infarction: a randomised clinical trial. Issue 12 (11th September 2021) - Liu, Yong; Tan, Ning; Huo, Yong; Chen, Shiqun; Liu, Jin; Chen, Yun-Dai; Wu, Keng; Wu, Guifu; Chen, Kaihong; Ye, Jianfeng; Liang, Yan; Feng, Xinwu; et al.
Abstract : Objective: To evaluate the efficacy of aggressive hydration compared with general hydration for contrast-induced acute kidney injury (CI-AKI) prevention among patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI). Methods: The Aggressive hydraTion in patients with STEMI undergoing pPCI to prevenT Contrast-Induced Acute Kidney Injury study is an open-label, randomised controlled study at 15 teaching hospitals in China. A total of 560 adult patients were randomly assigned (1:1) to receive aggressive hydration or general hydration treatment. Aggressive hydration group received preprocedural loading dose of 125/250 mL normal saline within 30 min, followed by postprocedural hydration performed for 4 hours under left ventricular end-diastolic pressure guidance and additional hydration until 24 hours after pPCI. General hydration group received ≤500 mL 0.9% saline at 1 mL/kg/hour for 6 hours after randomisation. The primary end point is CI-AKI, defined as a >25% or 0.5 mg/dL increased in serum creatinine from baseline during the first 48–72 hours after primary angioplasty. The safety end point is acute heart failure. Results: From July 2014 to May 2018, 469 patients were enrolled in the final analysis. CI-AKI occurred less frequently in aggressive hydration group than in general hydration group (21.8% vs 31.1%; risk ratio (RR) 0.70, 95% CI 0.52 to 0.96). Acute heart failure did not significantly differ between the aggressive hydration group and the general hydration group (8.1% vs 6.4%, RR 1.13, 95% CI 0.66 to 2.44). Several subgroup analysis showed the better effect of aggressive hydration in CI-AKI prevention in male, renal insufficient and non-anterior myocardial infarction participants. Conclusions: Comparing with general hydration, the peri-operative aggressive hydration seems to be safe and effective in preventing CI-AKI among patients with STEMI undergoing pPCI.